SMALL-SCALE HETEROGENEITY IN THE GEOCHEMISTRY OF SEAGRASS VEGETATED AND NON-VEGETATED ESTUARINE SEDIMENTS: CAUSES AND CONSEQUENCES - Hebert A.B.; Morse J.W.; Eldridge P.M. (My University, 2007)
In addition to nutrient and light availability, sedimentary biogeochemical processes can play an essential role in seagrass productivity. Previous investigations of the interactions between seagrasses and their underlying sediments have failed to clearly identify the spatio-temporal variability of the major geochemical parameters involved. Dissolved and solid phase chemical parameters in eelgrass vegetated and nearby non-vegetated sediments were investigated in this study to determine their vertical, lateral, and temporal distributions. Solid-state microelectrodes were used to investigate dissolved O2, ΣH2S, Fe2+, and Mn2+ on mm space scales. In this study, spatial heterogeneity was assessed and diurnal “ventilation” by seagrass productivity (i.e., the translocation of photosynthetically produced oxygen to the anoxic sedimentary environment) was not observed probably because benthic infaunal activity (bioturabation and bioirrigation) and microzones established by microbial processes led to highly heterogeneous sediment geochemistry where temporal variability was obscured by small-scale spatial variability. Non-vegetated sediments were less geochemically variable laterally than vegetated sediments, however, in some cases, they had similar vertical variability, possibly because they had been vegetated at an earlier time. This study demonstrates that in vegetated sediments where there is also substantial benthic macrofaunal activity it is difficult to separate the impacts of the two types of biota on sediment geochemistry and their spatial patterns, and it also raises the question of the applicability of traditional one-dimensional diagenetic models for such spatially–temporally complex sediments.
Keywords: SEAGRASS; SULFIDE; LIGHT; HETEROGENEITY; NUTRIENTS; CARBON; VOLTAMMETRY